The Berlin-Baghdad Express : The Ottoman Empire and Germany's Bid for World Power, 1898-1918 - McMeekin, Sean, 1974- (London Penguin Books, 2011)
Prior to the First World War, Germany sought the Ottoman Empire as an ally to create a jihad against the British. 'The Berlin-Baghdad Express' provides a fascinating account of Western interference in the Middle East and its lamentable results.
Includes Notes, Bibliography and Index.
Keywords: Turkey -- Germany -- Jihad